Factor influencing customer to choose mamak stall or restaurant as preferable restaurant / Hani Muhammad Hilmi Hanizam - Hanizam, Hani Muhammad Hilmi (Faculty of Business and Management, 2019)
Mamak restaurant has become the talk of the town with various cases regarding this kind of restaurant. So many issues come out when we search the internet about mamak restaurant and it is not a positive as well. From the dissatisfaction of the customers about the hygienic aspect of the restaurant, to the price that they charged on something that doesn’t makes any sense at all to the mind of the customers. The main objective of this study was to identify the factors influencing customers to choose mamak stall or restaurant as preferable restaurant. Hence, This study shows that overall for the independent variables consist of quality of physical environment, food quality, and service quality have significantly affects towards customer behavioral intention. Subsequent regression analyses demonstrated that the independent variable influence customers behavioral intention through the factors that affecting the customers. However, this study is to investigate the most effective factors effecting customers perceptions towards service and quality of mamak restaurant.